Boundary Value Problems for Fractional Differential Equations with Fractional Multiterm Integral Conditions - Jessada Tariboon; Sotiris K. Ntouyas; Arisa Singubol (Journal of Applied Mathematics)
We discuss the existence and uniqueness of solutions for boundary value problems involving multiterm fractional integral boundary conditions. Our study relies on standard fixed point theorems. Illustrative examples are also presented.